2022
DOI: 10.1136/bmjopen-2022-067461
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia as a predictor of outcome after transcatheter aortic valve implantation: protocol for systematic review and meta-analysis

Abstract: IntroductionSarcopenia represents a central biological substratum of frailty, which increases the incidence of adverse events and mortality after surgery for oesophageal cancer, gastrectomy and pancreatic surgery. Recently, sarcopenia has been suggested as a predictor of outcomes in patients undergoing transcatheter aortic valve implantation (TAVI). However, since relevant data were variable, we aimed to perform a systematic review and meta-analysis of the current literature to evaluate sarcopenia as a predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…There are limited data comparing XEN with trabeculectomy. The 2 procedures had similar IOP-lowering efficacy when the baseline IOP was in the low twenties; 133 whereas overall, trabeculectomy lowered IOP significantly more than the XEN 45 implant 134–136 …”
Section: Subconjunctival Spacementioning
confidence: 93%
See 1 more Smart Citation
“…There are limited data comparing XEN with trabeculectomy. The 2 procedures had similar IOP-lowering efficacy when the baseline IOP was in the low twenties; 133 whereas overall, trabeculectomy lowered IOP significantly more than the XEN 45 implant 134–136 …”
Section: Subconjunctival Spacementioning
confidence: 93%
“…The 2 procedures had similar IOP-lowering efficacy when the baseline IOP was in the low twenties; 133 whereas overall, trabeculectomy lowered IOP significantly more than the XEN 45 implant. [134][135][136] Comparing the XEN 45 and XEN 63, Fernandez-García et al 137 found no difference in the amount of IOP-lowering over 36 months. However, Evers et al 138 found a slightly lower IOP after XEN 63 (IOP reduction of 44.6% vs 40.1%).…”
Section: Outcome and Safetymentioning
confidence: 99%